2015
DOI: 10.1371/journal.pone.0144690
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Diarrhea Exhibits Spatiotemporal Variation in Northwest Ethiopia: A SaTScan Spatial Statistical Analysis

Abstract: BackgroundChildhood diarrhea continues to be a public health problem in developing countries, including Ethiopia. Detecting clusters and trends of childhood diarrhea is important to designing effective interventions. Therefore, this study aimed to investigate spatiotemporal clustering and seasonal variability of childhood diarrhea in northwest Ethiopia.MethodsRetrospective record review of childhood diarrhea was conducted using quarterly reported data to the district health office for the seven years period be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
4
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(76 citation statements)
references
References 58 publications
6
63
4
3
Order By: Relevance
“…The highest incidence rate was reported in 2018. Previous studies conducted in similar setting like in Rwanda contradict with the findings [20,21] whereby they reported a decrease tendency. However another study conducted in Ethiopia found similar findings [16].…”
Section: Discussioncontrasting
confidence: 65%
“…The highest incidence rate was reported in 2018. Previous studies conducted in similar setting like in Rwanda contradict with the findings [20,21] whereby they reported a decrease tendency. However another study conducted in Ethiopia found similar findings [16].…”
Section: Discussioncontrasting
confidence: 65%
“…The need to examine spatial and temporal patterns in the risk of childhood chronic malnutrition in this study has been motivated by previous studies that observed that certain health outcomes exhibit spatial, temporal, spatiotemporal and seasonal patterns and that such findings are crucial to public health policy 25 and to designing effective public health intervention, treatment and prevention strategies. [13,14,10,12,15,16,9,11] Specifically, a study conducted in northwest Ethiopia to examine spatiotemporal clustering and seasonal differences in…”
Section: A N U S C R I P T Highlightsmentioning
confidence: 99%
“…childhood diarrhoea reported substantial spatial, temporal, and spatiotemporal clustering. [14] A study conducted in Mexico to investigate spatiotemporal pat-30 terns of diarrhoeal mortality also observed spatiotemporal trends [13]. A study conducted in Somalia to examine wasting among children aged below 5 years reported substantial spatial and temporal variability in wasting.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The maximum-size specified the percentage of the maximum total population at risk within the scanning window [29]. In this research, considering the human population density and the size of each county, the maximum cluster size was set to 50%.…”
Section: Methodsmentioning
confidence: 99%
“…Discrete Poisson Model was used to identify the cluster locations of HFRS cases in a specific window. Moreover, SaTScan program was used to implement the scan statistical analysis [29–32]. …”
Section: Methodsmentioning
confidence: 99%